Antiprotozoal Effects of Pediococcus acidilactici-Derived Postbiotic on Blastocystis Subtypes ST1/ST3 - Aydemir, Selahattin; Arvas, Yunus Emre; Aydemir, Mehmet Emin; Barlık, Fethi; Gürbüz, Esra; Yazgan, Yener; Ekici, Abdurrahman (MDPI AG, 2025)
Blastocystis, a common intestinal protozoan in humans, is associated with gastrointestinal disorders, irritable bowel syndrome, urticaria, and colorectal cancer. Its genetic diversity and potential for treatment resistance make it a focus of ongoing research. This study evaluated the in vitro antiprotozoal activity of a postbiotic derived from Pediococcus acidilactici as a natural alternative treatment. P. acidilactici cultures were grown in MRS broth under anaerobic conditions, and the postbiotic was collected and characterized for pH, yield, organic acid composition, and phenolic compound content. Human isolates of Blastocystis subtypes ST1 and ST3 were cultured in Jones’ medium and exposed to varying postbiotic concentrations for 72 h. Viability was assessed microscopically. The cytotoxic effect of the postbiotic-derived P. acidilactici was evaluated by investigating its impact on the viability of HT-29 cells using the Cell Counting Kit 8. The postbiotic showed a 7% yield and a pH of 4.52 ± 0.11. It contained seven different organic acids, predominantly lactic acid, and eleven phenolic compounds, with naringin as the most abundant. At 4.38 mg/mL, the postbiotic achieved over 94% inhibition and 100% inhibition at 8.75 mg/mL and above. A pH analysis confirmed that the inhibition was independent of the culture medium acidity. Cell viability was not affected at the postbiotic concentration showing 100% antiprotozoal activity (8.75 mg/mL). These findings suggest that the P. acidilactici postbiotic is effective on a mixed culture of ST1 and ST3 subtypes and holds promise as a safe, natural antiprotozoal agent. Further in vivo studies are needed to confirm this.
Keywords: Blastocystis; organic acid; viability; postbiotic; antiparasite; R; Medicine; Article